Microstructure and Magnetic Anisotropy of SmCo‐Based Films Prepared via External Magnetic Field Assisted Magnetron Sputtering. Issue 5 (20th February 2022) - Li, Hao; Wei, Lu; Hong, Yuan; Zhang, Yuanwei; Qiu, Zhaoguo; Wang, Gang; Zhao, Lizhong; Liu, Xiaolian; Zhang, Xuefeng; Chen, Deyang; Zheng, Z. G.; Xia, Weixing; et al.
Abstract : SmCo‐based thin films have excellent permanent magnetic properties for application in magnetic functional devices. The conventional methods to control the magnetic anisotropy are inserting the suitable buffer layer or applying magnetic field heat treatment. However, the selection of the buffer layer and the thickness of the SmCo layer are limited. Additionally, the magnetic field heat treatment is detrimental to suppressing the grain growth. Herein, the SmCo‐based thin films by magnetic field assisted magnetron sputtering followed by a rapid thermal annealing (RTA) is prepared. The characteristic diffraction peak of SmCo5 (200) with in‐plane orientation disappears, indicating that the in‐plane magnetic anisotropy could be further decreased. Meanwhile, the out‐of‐plane coercivity highly increases when applying an external magnetic field, which is contributed partly by the refined SmCo grains under the external magnetic field due to the reduction of critical free energy of Sm–Co cluster nucleation. Furthermore, micromagnetic simulations indicates that the out‐of‐plane magnetic moments of Sm2 Co17 phase are more difficult to reverse because the ratio of in‐plane and out‐of‐plane oriented moments changed from 1:1 to 1:1.4, and proves that the proportion of magnetic moment direction is significant to control magnetic anisotropy and coercivity which is consistent with the experiment results. Abstract : The magnetic anisotropy of SmCo‐based thin films varying from in‐plane to partially out‐of‐plane direction is successfully controlled and the grain size of SmCo films is refined via the magnetic field assisted magnetron sputtering. The micromagnetic simulations are applied to demonstrate that the proportion of magnetic moment direction is significant to control magnetic anisotropy and coercivity.